Pengujian Kinerja Cooling Water untuk Mesin Stirling tipe Gamma Skala Kecil - Prasetio, Indra; Jufrizal, Jufrizal; Supriatno, Supriatno (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
This study aims to evaluate and analyze the performance of cooling water in a small-scale Gamma-type Stirling engine. The research method employed was an experimental approach. The test results show that the inlet water temperature was 27.6 °C, while the average outlet water temperature reached 92.33 °C after 60 minutes of testing. Cooling water with an inlet temperature of 27.6 °C reduced the average heat source temperature from 484.51 °C to 64.78 °C on the compression chamber side. At an airflow rate of 0.006 m³/s, the average cooling effectiveness was recorded at 13%, with the highest value of 19.1% observed at the 55th minute of testing. This study concludes that cooling water effectively reduces the heat source temperature and improves thermal efficiency in a small-scale Gamma-type Stirling engine.